Investigate the chemical content of (Syrian) green tea plant extract Camellia Sinensis by ethanol (Latakia University Journal -Basic Sciences Series, 2024)
Analysis of green tea leaves sample abstracted using Soxhlet Using ethanol as a solvent apparatus via GC/MS device has showed existence of 24 products From three different regions (Banias - Bustan Al-Basha - Damsarkho) It represented 46.69% for Banias, 17.66% for Bustan Al-Basha, and 33.65% for Damsarkho, and it was as follows: In Damsarkho, 15.20% nitrogen-based compounds, 1.13% hydrocarbons, 15.42% phenolic compounds, and 1.90 % of the residual. In Banias, 7.52% nitrogen-based compounds, 3.39% hydrocarbons, and 35.78% phenolic compounds. In Bustan Al-Basha, 12.62% nitrogen-based compounds, 2.35% hydrocarbons, 2.69% phenolic compounds. furthermore, Analysis of green tea leaves sample abstracted using ultrasonic device ethanol as a solvent apparatus via GC/MS device has showed the presence of 20 compounds represented 38.17% for Banias, 18.91% for Bustan al-Basha, and 31.91% for Damsarkho, and it was as follows: In Damsarkho, 12.19% nitrogen-based compounds, 14.74% hydrocarbons, 4.98% phenolic compounds, and in Banias, 6.24% nitrogen-based compounds, 1.46% hydrocarbons, 30.47% phenolic compounds, and in Bustan Al-Basha, 4.02% nitrogen-based compounds, 1.36% hydrocarbons, 11.78% phenolic compounds, and 1.75% of the residual.